1998
DOI: 10.1038/sj.ijo.0800664
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral fat metabolism during infusion of an exogeneous triacylglycerol emulsion

Abstract: OBJECTIVE: To test the hypothesis that intravenous infusion of lipid would bring about changes in adipose tissue metabolism, which would tend to spare net fat mobilization, and to attempt to identify the mediators of such responses. DESIGN: The triacylglycerol (TG) emulsion, Intralipid, was infused and metablic changes in subcutaneous adipose tissue and forearm muscle were assessed by measurements of arterio-venous differences. SUBJECTS: Six normal male subjects aged 21 ± 37 y, with body mass index (BMI) 23.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 41 publications
6
20
1
Order By: Relevance
“…The duration of the infusion suggests that this may be due to direct gene transactivation, probably by PPA R-2. Interesti n g l y, mean plasma leptin levels were unaffected by the 5-h Intralipid plus heparin (2.8 ± 0.4 ng/ml) or saline infusion (2.9 ± 0.9 ng/ml) in comparison with baseline (3.2 ± 0.6 and 3.2 ±1.0 ng/ml, respectively), thus confirming the results obtained by Samra et al (26).…”
Section: R E S U Lt Ssupporting
confidence: 88%
See 2 more Smart Citations
“…The duration of the infusion suggests that this may be due to direct gene transactivation, probably by PPA R-2. Interesti n g l y, mean plasma leptin levels were unaffected by the 5-h Intralipid plus heparin (2.8 ± 0.4 ng/ml) or saline infusion (2.9 ± 0.9 ng/ml) in comparison with baseline (3.2 ± 0.6 and 3.2 ±1.0 ng/ml, respectively), thus confirming the results obtained by Samra et al (26).…”
Section: R E S U Lt Ssupporting
confidence: 88%
“…Under our experimental conditions, it is unlikely that NEFA-induced leptin gene expression influenced the rate of lipolysis, since it has been shown that increased NEFA availability from an extracellular source inhibits intracellular lipolysis (26,39). The intracellular role of N E FA-induced leptin gene expression may rather be that of modulating the expression of other genes involved in the regulation of cell metabolism.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…They concluded that changes in leptin concentration were not correlated with changes in FFA concentration. Samra et al 34 showed consistent leptin release, with no change over time, following the onset of an Intralipid triacylglycerol (TG) infusion. These authors observe, however, that the TG extraction by adipose tissue was much less that that observed when TG concentration is elevated by ingestion of a fatty meal.…”
Section: Discussionmentioning
confidence: 99%
“…This is clearly an unphysiological situation, but if it is mimicked acutely by intravenous infusion of a TG emulsion, producing no detectable increase in plasma insulin, there is a marked decrease in NEFA release from adipose tissue, reflecting a suppression of HSL activity. 168,169 This experiment seems to imply that there is some signal that responds to increased nutrient availability to regulate net fat storage independently of insulin, and in this case presumably also independently of the SNS.…”
Section: Pulsatilitymentioning
confidence: 96%